齿轮新旧标准精度结构和精度指标关系分析 - 桂定一 (Jixie chuandong)
The structure and tolerance limitation are analized and compared for the new and former national standard on gear accurany. The conception of “equivalent function” is presented. The shortcoming of old standard and the advantage of new standard are presented.